A Generalization of Meir-Keeler Type Common Fixed Point Theorem For Four Noncontinuous Mappings - Popa, Valeriu (Sarajevo Journal of Mathematics, 2024)
In this paper, using a combination of methods used in [1], [20] and [22] the results from [3, Theorem 1], [14, Theorem 1] and [15, Theorem 1] are improved removing the assumption of continuity, relaxing compatibility to the weak compatibility property and replacing the completeness of the space with a set of four alternative conditions for four functions satisfying an implicit relation. 2000 Mathematics Subject Classification. 54H25